RAPD optimization for genetic studies with Citrulus lanatus and Sesamum indicum genotypes - Di Mauro, Antonio Orlando [UNESP]; Di Mauro, Daniela Cristina [UNESP]; Capeloto, Andrea [UNESP]; Arriel, Nair Helena de Castro; Costa, Marcelo Marchi [UNESP]; Trevisoli, Sandra Helena Uneda; Di Mauro, Sonia Marli Zingaretti [UNESP] (Byte Systems - Solucoes Digitais, 2006)
The Random Amplified Polymorphic DNA (RAPD) technique is powerful for DNA polymorphism determinations and is widely used in research involving different organisms, but it is known that RAPD can be affected by many factors that may result in false positive bands and non-reproducible assays. In this study, we analyzed the effect of several factors such as DNA template, primer and Taq DNA polymerase concentrations to optimize and standardize the RAPD technique for further genetic studies with Citrulus lanattus and Sesamum indicum L. The best combination of DNA, Taq DNA polymerase enzyme and primer concentrations in RAPD amplification procedures for sesame and watermelon genotypes was established.
Keywords: Conditions, watermelon, sesame; DNA amplification; Citrullus lanatus var. lanatus; Sesamum indicum